THE BRANDING POTENTIAL OF BUCHAREST: STRATEGY AND SUCCESS FACTORS - POPESCU, Ruxandra Irina (Theoretical and Empirical Researches in Urban Management, 2009)
Bucharest is still looking for its identity. Reported in the national brand – that is still in an incipient phase, it can play two roles: whether as ingredient for the country brand, the capital becoming an element included on the list of values promoted at national level, or as a landmark, for defining and subsequently for improving the country brand. The unexploited potential must be capitalized in the future by using urban branding and marketing steps adapted to the local specificity.